Efficient, versatile and practical palladium-catalyzed highly regioselective ortho-halogenation of azoxybenzenes. Issue 1 (17th November 2015) - Sun, Meng; Chen, Xiangxiang; Zhang, Liang; Sun, Wei; Wang, Zhe; Guo, Peiyu; Li, Ya-Min; Yang, Xiao-Juan
Abstract : A highly efficient and practical strategy of regio-selective ortho -halogenation of azoxybenzenes with NXS in the presence of palladium catalysts has been developed in good to excellent yields. Abstract : A highly efficient and practical strategy for regio-selective ortho -halogenation (I, Br, Cl) of azoxybenzenes with NXS in the presence of palladium catalysts has been developed in good to excellent yields. The reaction proceeds smoothly and can tolerate a variety of functional groups. Moreover, this chemistry can be applied to substrates in at least a gram scale.